2023
DOI: 10.1101/2023.10.19.563191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of Grp170 results in catastrophic disruption of endoplasmic reticulum functions

Melissa J. Mann,
Chris Melendez-Suchi,
Maria Sukhoplyasova
et al.

Abstract: GRP170, a product of the Hyou1 gene, is required for mouse embryonic development, and its ablation in kidney nephrons leads to renal failure. Unlike most chaperones, GRP170 is the lone member of its chaperone family in the ER lumen. However, the cellular requirement for GRP170, which both binds non-native proteins and acts as nucleotide exchange factor for BiP, is poorly understood. Here, we report on the isolation of embryonic fibroblasts from mice in which LoxP sites were engineered in the Hyou1 loci (Hyou1L… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…In addition, the GRP170 NT-/- animals developed albuminuria and glucosuria, hallmarks of PT injury, and renal histology revealed features consistent with PT injury. As predicted based on our prior work, the loss of GRP170 also altered nephron channel stability and trafficking, especially in the proximal nephron(22, 23, 38).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the GRP170 NT-/- animals developed albuminuria and glucosuria, hallmarks of PT injury, and renal histology revealed features consistent with PT injury. As predicted based on our prior work, the loss of GRP170 also altered nephron channel stability and trafficking, especially in the proximal nephron(22, 23, 38).…”
Section: Introductionsupporting
confidence: 78%
“…UPR activation and GRP170 expression have also been linked to numerous disease states, including ischemic injury, diabetes, diabetic nephropathy, cancer, and neurodegenerative disease (27, 32, 54–58). We also recently showed that the progressive loss of GRP170 is accompanied by UPR activation and induction of apoptotic markers in mouse embryo fibroblasts (38). Therefore, we asked if a HS diet tempers UPR activation as a result of the downstream consequence of the amelioration of select kidney injury markers in GRP170 NT-/- mice (see above).…”
Section: Resultsmentioning
confidence: 89%